REFORMASI MANAJEMEN ADMINISTRASI PENDIDIKAN ISLAM DI ERA TATA KELOLA DIGITAL - Sofyan Mustoip; Yuriska Dewi Suwarno; Khotibul Umam (Universitas Islam Bunga Bangsa Cirebon, 2022)
The administrative management of Islamic educational institutions is undergoing profound transformation driven by the rapid proliferation of digital technologies and evolving governance expectations. Despite widespread acknowledgment that digital transformation is reshaping educational administration globally, the specific dynamics of this process within Islamic educational settings in Indonesia remain insufficiently documented and theorized. This study aims to examine the reform of administrative management in Islamic educational institutions within the context of digital governance, identifying the drivers, dimensions, and implications of this transformation. A systematic library research methodology was employed, utilizing peer-reviewed journal articles, academic books, and policy documents published between 2019 and 2024. The findings indicate that digital governance reform in Islamic educational administration encompasses three interconnected dimensions: technological adoption, institutional restructuring, and value alignment. A significant research gap was identified in the absence of frameworks that reconcile digital governance imperatives with the normative values of Islamic institutional management. This study proposes the Digital-Islamic Governance Integration (DIGI) model as a conceptual contribution toward bridging this gap.